COVID-19 Lockdown and Social Distancing Policies and the Sustainability of Small Businesses in South-Eastern Nigeria. (2nd October 2021) - Iwuoha, Victor Chidubem; Aniche, Ernest Toochi
ABSTRACT: This study explores the experience of small business operators in South-Eastern Nigeria to underscore the sub-sectoral effects of COVID-19 lockdown measures on small businesses. Although COVID-19 lockdown and social distancing policies are generally perceived to have negative effects on small businesses, this study argues that these policies have had both positive and negative effects on small businesses. Clustering small businesses into three categories: fashion/event, food/drug and general merchandise, the study depicts a cross-sectoral disparity in the patronage level and income streams of small businesses. While the fashion/event businesses experience very low sales and poor performances, the food/drug businesses record high sales/improved performances, and the general merchandise maintains normal sales/performances. The study observes gaps in government's COVID-19 intervention policies and initiatives (palliatives) on small businesses and proposes new policy directions to cushion the negative impact of lockdown measures and fast track the sustainability of small businesses in post-COVID-19 period.